The Vampire Effect: The Role of Humour and Involvement Level in Advertisement Recall and Recognition - Dobbelstein, Thomas; Oberluggauer, Teresa; Mason, Roger B. (International Review of Management and Marketing, 2025)
The effect of humour on brand and product recall and recognition in advertising, and the consumer’s level of involvement, were studied by examining the “vampire effect,” wherein factors, such as humour, draw attention away from an advertising message. A descriptive, cross-sectional quantitative online survey using convenience and snowball sampling recruited 443 participants, who assessed the humorousness of six advertisements, were asked to recall the advertisements without prompts, and then to identify those recognized from a list of brand names. The study showed that humour in an advertisement negatively influenced brand recall and recognition and also reduced product recall and recognition. In both cases, respondents were less able to remember the products and brands in the humorous advertisements. Furthermore, people with low involvement in the advertised product category were more affected by the vampire effect and so were less likely to remember the product or brand. Finally, recommendations are provided for when humour in advertising is appropriate and when not. The study is important because, although there is much research on effectiveness of advertisements, especially recall and recognition, there is relatively little research on the vampire effect, and almost nothing on the vampire effect of humour in advertising.